Displaying Religious Image on Youtube: Ganjar Pranowo's Political Communication Strategy on Social Media - Zulhazmi, Abraham Zakky (DINIKA : Academic Journal of Islamic Studies, 2020)
The dynamics of political communication are becoming increasingly attractive in today's digital era. Marked by the widespread use of social media by politicians, vlog (video blog) has been widely popular among youngsters. Its popularity increases once the President of Indonesia, Joko Widodo, took part in using the platform. Besides Joko Widodo, the Governor of Central Java, Ganjar Pranowo also used vlogs as a means of political communication. Using semiotic analysis of Roland Barthes, this research aims at revealing the image that Ganjar Pranowo wants to display through his vlogs. The study concludes how Ganjar wants to be perceived as a religious, popular, and contemporary person through the vlogs he uploaded on his Youtube channel. Religious image needed to be displayed considering that Ganjar is from a nationalist party (PDIP) while political opponents of President Joko Widodo (Ganjar's colleague at PDIP) are building the impression of Joko Widodo as anti-Islam. It was important for Ganjar to show himself as an egalitarian and a populist because he had an interest in the 2018 Central Java governor election.Ganjar utilizes a vlog to display him being up to date. This is important for Ganjar to attract sympathy from the millennials.